2023
DOI: 10.1088/2632-072x/acbd7d
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of online social rhythms via avatar communications

Abstract: In this study, we consider users' online communication rhythms (online social rhythms) as coupled oscillators in a complex social network. Users' rhythms may be entrained onto those of their friends, and macro-scale pattern of such rhythms can emerge. We investigated the entrainment in online social rhythms and long-range correlations of the rhythms using an avatar communication dataset. We indicated entrainment in online social rhythms to emerge if the strength of a new connection reaches a threshold. This en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This is available for iOS and Android devices. A previous study [2] indicated the entrainment of online social rhythms among Pigg Party players.…”
Section: Pigg Partymentioning
confidence: 92%
See 4 more Smart Citations
“…This is available for iOS and Android devices. A previous study [2] indicated the entrainment of online social rhythms among Pigg Party players.…”
Section: Pigg Partymentioning
confidence: 92%
“…We builted online social networks to study the intervention effects on participants' neighbors for each week, based on a previous study [2]. Therefore, we acquired five networks for the weeks of intervention periods 6 .…”
Section: Participants' Neighborsmentioning
confidence: 99%
See 3 more Smart Citations